PUBLIC SENTIMENT TOWARDS VEILED PREACHERS: A STUDY OF THE FUNCTION OF ISLAMIC COMMUNICATION BASED ON THE QURAN - Nona Khairah; Abdullah Abdullah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to examine public sentiment towards niqab-wearing preachers and the challenges and opportunities for niqab-wearing preachers in preaching and to examine the function of Islamic communication based on the perspective of the Qur'an. The approach used is qualitative-descriptive with field research methods through in-depth interviews, observations, and documentation studies. The study was conducted in Gang Sukadamai Tengah, Kelambir V, with six informants consisting of niqab-wearing preachers and the local community. The results of the study indicate that public sentiment towards niqab-wearing preachers is ambivalent, including positive and negative biases. Positive bias appears in the form of appreciation for piety, consistency in religion, and increased information on preaching. Conversely, negative bias includes the assumption that the niqab is a symbol of foreign culture, is associated with radicalism, and is considered to create social distance. Despite facing challenges in the form of stigma and social prejudice, niqab-wearing preachers still have strong opportunities for preaching through consistency of values, strong religious symbols, and an inclusive and polite communication approach. This study concludes that the effectiveness of the communication of the da'wah of the veiled da'ah is very dependent on the ability to balance religious symbols with social openness, as per the principle of rahmatan lil alamin in the Qur'an.